Global incidence trends of early-onset colorectal cancer and related exposures in early-life: an ecological analysis based on the GBD 2019 - Wang, Ziyang; Yao, Weiyuan; Wu, Weimiao; Huang, Junjie; Ma, Yanlei; Yang, Chen; Shi, Jufang; Fu, Jiongxing; Wang, Yingying; Wong, Martin C. S.; Xu, Wanghong (Frontiers in Public Health, 2024)
Background The incidence of early-onset colorectal cancer (EOCRC) is increasing globally. This study aims to describe the temporal trends of incidence and explore related risk exposures in early-life at the country level based on the GBD 2019. Methods Data on the incidence and attributable risk factors of EOCRC were obtained from the GBD 2019. Temporal trends of age-standardized incidence were evaluated by average annual percentage change (AAPC). Early-life exposures were indicated as summary exposure values (SEV) of selected factors, SDI and GDP per capita in previous decades and at ages 0–4, 5–9, 10–14 and 15–19 years. Weighted linear or non-linear regressions were applied to evaluate the ecological aggregate associations of the exposures with incidences of EOCRC. Results The global age-standardized incidence of EOCRC increased from 3.05 (3.03, 3.07) to 3.85 (3.83, 3.86) per 100,000 during 1990 and 2019. The incidence was higher in countries with high socioeconomic levels, and increased drastically in countries in East Asia and Caribbean, particularly Jamaica, Saudi Arabia and Vietnam. The GDP per capita, SDI, and SEVs of iron deficiency, alcohol use, high body-mass index, and child growth failure in earlier years were more closely related with the incidences of EOCRC in 2019. Exposures at ages 0–4, 5–9, 10–14 and 15–19 years were also associated with the incidences, particularly for the exposures at ages 15–19 years. Conclusion The global incidence of EOCRC increased during past three decades. The large variations at regional and national level may be related with the distribution of risk exposures in early life.